Heuristic method for relay node placement in heterogeneous wireless network - Guffens, Eliott; Le Nir, Vincent; Lauwens, Ben; Becquaert, Mathias (Frontiers in Communications and Networks, 2025)
Whether it is to initially deploy a network or to restore the connectivity in a partitioned one, the question of the optimal Relay Node (RN) placement arises. This problem is already challenging when considering a static homogeneous network. However, diversity in transmission parameters within the network can induce diversity in transmission ranges, imposing the consideration of heterogeneity in the network. Furthermore, if the nodes are moving, the RN placement scheme must manage a smooth repositioning of the RNs without any large jumps or major restructuring. This paper introduces an effective strategy for deploying the minimum number of RNs in order to restore the connectivity between the nodes of a partitioned heterogeneous network. Through the statistical analysis of results from numerous randomly generated scenarios, the proposed Barycenter-focused Relay nodes placement for Heterogeneous wireless Networks (BRHEN) algorithm is shown to be an improvement on other similar approaches in terms of the number of RNs and the latency. Additionally, BRHEN exhibits stability in the positions and number of RNs when small displacements are applied to the Initial Nodes (INs). This characteristic makes this method suitable for scenarios with moving INs.